Ezrin expression combined with MSI status in prognostication of stage II colorectal cancer - Slik K; Kurki S; Korpela T; Carpen O; Korkeila E; Sundstrom J (PUBLIC LIBRARY SCIENCE, 2022)
Currently used factors predicting disease recurrence in stage II colorectal cancer patients are not optimal for risk stratification. Thus, new biomarkers are needed. In this study the applicability of ezrin protein expression together with MSI status and BRAF mutation status were tested in predicting disease outcome in stage II colorectal cancer. The study population consisted of 173 stage II colorectal cancer patients. Paraffin-embedded cancer tissue material from surgical specimens was used to construct tissue microarrays (TMAs) with next-generation technique. The TMA-slides were subjected to following immunohistochemical stainings: MLH1, MSH2, MSH6, PMS2, ezrin and anti-BRAF V600E antibody. The staining results were correlated with clinicopathological variables and survival. In categorical analysis, high ezrin protein expression correlated with poor disease-specific survival (p = 0.038). In univariate analysis patients having microsatellite instabile / low ezrin expression tumors had a significantly longer disease-specific survival than patients having microsatellite stable / high ezrin expression tumors (p = 0.007). In multivariate survival analysis, the presence of BRAF mutation was associated to poor overall survival (p = 0.028, HR 3.29, 95% CI1.14-9.54). High ezrin protein expression in patients with microsatellite stable tumors was linked to poor disease-specific survival (p = 0.01, HR 5.68, 95% CI 1.53-21.12). Ezrin protein expression is a promising biomarker in estimating the outcome of stage II colorectal cancer patients. When combined with microsatellite status its ability in predicting disease outcome is further improved.